Words and Pattern Phrases Related to Women in Karakhanid Turkish Texts - Aslı Zengin (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Karakhanid Turkish is an expression that represents a language period in which the Turks began to “differentiate” within the framework of geographical, cultural, economic, sociological, and religious beliefs. Language heirlooms belonging to this period consist of the Kutadgu Bilig, Dîvânu Lugâti't-Türk, Atebetü'l-Hakâyık, and Qur'an Translations. This study examines the concept of women found in these works and evaluates these concepts within the framework of the nomenclature used for women. Women have always stood out in the pre-Islamic Turkish state and society. This study presents the vocabulary that shows the position of women as having a crucial place in society before the adoption of Islam. The congenital and acquired names of “woman” will be included. Furthermore, the study also provides information about the forms and usage of these words in the Old Turkish period. It will be determined if new words have been added since then and if there are words that differ in meaning. The identified words—names given to women during the Karakhanid Turkish period—will be examined and analyzed comparatively among the ancient works.